Evaluation of the Use of Antidiarrheal Drugs and Antibiotics in Inpatients at a Number of Hospitals - Maharani, Dhavina; Hilmi, Indah Laily (Jurnal EduHealth, 2022)
Diarrhea is one of the health problems that are often faced by the community, usually caused by microorganisms such as bacteria, parasites, viruses, and protozoa that are transmitted between individuals through the fecal-oral route. The handling of diarrhea recommended by WHO is referred to as cross-management of diarrhea by providing rehydration, zinc supplements, nutrition, antibiotics and education for parents or caregivers. The research method used is to collect several articles from the latest published journals which were then reviewed and reviewed. The purpose of this review article is to know the evaluation of the use of antidiarrheal drugs and antibiotics based on categories of inpatients in several hospitals. The results show that the prevalence of diarrhea in patients is dominated by men with an age range of 0-14 in children and the elderly over 50 years. Diarrhea can be managed by giving rehydration, zinc supplements, nutritional therapy, antibiotics, antidiarrheals, antipyretics, analgesics and antiemetics to reduce the symptoms and duration of diarrhea. Diarrhea therapy at several health facilities has shown quite good results through evaluation of drug administration through several observations including the right indication, right patient, right drug, right dose, right administration and right time of administration.